The Growth of Two Cultivars Mung Bean under different Sweet Corn Shelter Density in Sandy Soil Coastal Area - Dwi Astutik; Prapto Yudono; Sriyanto Waluyo (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
The experiment had been conducted from August to November 2016 at Samas sandy soil coastal area. The research aimed to determine growth response of mung bean sheltered by various density of sweet corn on coastal sandy soil. The experiment used the nested design with two factors with three replications.The first factor was density of sweet corn as shelter consisting of without shelter (S0), planting space of 15 × 40 cm (S1), and planting space of 30 × 40 cm (S2). The second factor was mung bean cultivars compiled of Vima 1 (V1) and Purworejo local cultivar (V2). The data of soil temperature, soil moisture content at the depth of 10 and 20 cm, soil salt content at 10 and 20 cm depth, leaf fresh and dry weight, root fresh and dry wieght, plant fresh and dry weight were collected. The effect of shelter density was on the leaves dry weight at 6 week after planting (WAP), meanwhile the mung bean cultivars influenced the soil moisture at 10 and 20 cm depth; leaves fresh weight, leaves dry weight, root fresh weight, and plant dry weight at 4 WAP. Vima 1 resulted in significantly higher compared to Purworejo local cultivar on soil moisture content in 10 and 20 cm, leaves fresh and dry weight, root fresh weight, plant fresh and dry weight at 4 WAP. There was interaction between sweet corn shelter density and mung bean cultivar on soil salt content at 10 cm (2 WAP), 20 cm (6 WAP), plant fresh weight at 4 and 6 WAP, and plant dry weight at 6 WAP. The best growth of mung bean was observed under higher level density shelter with 15 × 40 cm square planting space due to the deeper soil layer and lower salt content.